The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/bs12100371
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing Pregnancy during the COVID-19 Lockdown in Poland: A Cross-Sectional Study of the Mediating Effect of Resiliency on Prenatal Depression Symptoms

Abstract: The COVID-19 pandemic in Poland brought uncertainty, not only to the general population but also to women preparing for childbirth, which increased the risk of mental health illnesses during this special period of life. Resilience, which refers to positive adaptation or the ability to maintain good mental health, can be a protective factor against the development of psychiatric problems such as depressive symptoms. This study aimed to assess the protective role of resilience in the relationship of such risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
(73 reference statements)
1
4
1
Order By: Relevance
“…The loss of the feeling 'we are all in this together' that prevailed during the group sessions, may have contributed to lower perceived social support [36]. This supports the results of other studies, confirming the strong need to implement social interventions among new parents [23,33,36].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The loss of the feeling 'we are all in this together' that prevailed during the group sessions, may have contributed to lower perceived social support [36]. This supports the results of other studies, confirming the strong need to implement social interventions among new parents [23,33,36].…”
Section: Discussionsupporting
confidence: 83%
“…This study enrolled during the outbreak of the COVID-19 pandemic, where professional support became more critical but at the same time less accessible [22]. Building resilience is an important element of mental health promotion interventions for pregnant women, especially in such crises as the COVID-19 pandemic [23,24]. By integrating a resilience-oriented approach into prevention strategies, we expect to contribute to the wellbeing of pregnant women and their families.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we could not verify whether resilience has a mediating effect between COVID-19-related anxiety and depression and labour anxiety. Our findings are in contrast to Polish studies conducted during the pandemic that have investigated the mediating effect of resilience between pandemic stress and depressive symptoms [49]. Indeed, we used a different approach to measure stress related to the COVID-19 pandemic, which may be one of the reasons for this discrepancy.…”
Section: Discussioncontrasting
confidence: 77%
“…In our research, approximately one-third of the women in the study population reported depressive symptoms. When making comparisons with the Polish population, although these rates are higher than before the pandemic [48], our study identified lower rates of depression than Studniczek and Kossakowska at an earlier stage of the pandemic [49]. This disparity may be due to two reasons.…”
Section: Discussionmentioning
confidence: 55%
“…10 Consistent with findings in other contexts, resilience has been demonstrated to buffer against the negative psychosocial impacts of the COVID-19 pandemic. 4,11,12 However, given the recent increase in mental health disorders across various populations during and following the pandemic, it has been posited that this might reflect a population-level deterioration in resilience. 13 This is contrary to the general supposition that resilience is an intrinsic, trait-level characteristic that is stable without targeted intervention.…”
mentioning
confidence: 99%